2021
DOI: 10.51470/plantarchives.2021.v21.no1.137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Different Solvents for Phytochemical Constituents and Antioxidants Activity of the Leaves of Murraya Koenigii (Linn.) Spreng. (Rutaceae)

Abstract: Murraya koenigii (Rutaceae) is a promising source of bioactive compounds since the leaves of this plant has been traditionally used extensively in the Indian Ayurvedic system of medicine for the treatment of a wide range of diseases and disorders. Although the pharmacological effect of the plant’s bioactive compounds has been extensively studied, however, study on the effect of using different extraction solvents to extract these bioactive componentsis scarce. The aim of the present study was to evaluate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Obtained results was supported by Sablania et al (2019) in which Aq extract of curry leaves showed higher activity than MeOH and Ace at 1000 µg/mL of extract concentration. In a study conducted by (Ali et al, 2021), it was found that the MeOH extract exhibited the highest potency in terms of antioxidant radical scavenging activity at 93±0.65%, followed by ethanol at 81±0.13% (Truong et al, 2019) reported Ace (66.1%); MeOH (50.7%) showed scavenging activity/total antioxidant activity curry leaves at 100µg/ml concentrations. Figure 2 illustrates DPPH radical scavenging activity of leaves extract of S. asoca, O. basilicum, and M. koenigii.…”
Section: Radical Scavenging Activitymentioning
confidence: 97%
“…Obtained results was supported by Sablania et al (2019) in which Aq extract of curry leaves showed higher activity than MeOH and Ace at 1000 µg/mL of extract concentration. In a study conducted by (Ali et al, 2021), it was found that the MeOH extract exhibited the highest potency in terms of antioxidant radical scavenging activity at 93±0.65%, followed by ethanol at 81±0.13% (Truong et al, 2019) reported Ace (66.1%); MeOH (50.7%) showed scavenging activity/total antioxidant activity curry leaves at 100µg/ml concentrations. Figure 2 illustrates DPPH radical scavenging activity of leaves extract of S. asoca, O. basilicum, and M. koenigii.…”
Section: Radical Scavenging Activitymentioning
confidence: 97%
“…T. occidentalis is a nutritious vegetable widely cultivated for its palatable and nutritious leaves and seeds and contains essential nutrients that can play a major role in human nutrition [8,9]. T. occidentalis find numerous applications in different industries, such as food and medicine [10][11][12]. The leaves of T. occidentalis are good sources of phenolic compounds, essential amino acids, vitamins, minerals, proteins, antioxidants, and other essential nutrients, which [13] can play a regulatory and functional role.…”
Section: Introductionmentioning
confidence: 99%